SECURE AUDIO FILES USING VIGENERE CIPHER AND PLAYFAIR CIPHER - Sumadi, Muhammad Taufiq; Zahir S, Achmad Nur; Faldi, Faldi (Informatika, Universitas Jenderal Soedirman, 2024)
This study aims to maintain the confidentiality of audio files sent using a combination of the Playfair cipher and Vigenere cipher methods. In this research, the object of research is an audio file with the extension wave or *.wav. This research requires several stages, including Audio Data Analysis, Determination of System Architecture, Implementation, Testing, and Results Analysis. The results of this study indicate that in the Vigenere Cipher 256 Encryption in audio wave files, the audio messages conveyed sound unclear or have no meaning. From the 6 trial datasets based on analysis of MAE and PSNR, the average value of the encryption process at PSNR was 28.345, and MAE was 97.0625. The average value of the decryption process on PSNR and MAE is 0.0, indicating that the decryption process is successful. The speed of the encryption and decryption process is affected by the audio file's size, which means that the larger the file size, the longer the encryption and decryption time.